INTEGRASI FMEA DAN NEW SEVEN TOOLS UNTUK OPTIMALISASI PENGGUNAAN BAHAN BAKAR BOILER - Endik Wirawan; Nur Muflihah (INVANTRI (Inovasi Dan Pengelolaan Industri), 2022)
Abstract PT. XYZ is a sugar producing company with a production capacity of 12,000 TCD (Ton Cane per Day). To be able to compete with its more experienced competitors, PT. XYZ needs a proper strategy. One of these strategies is to maintain and continuously improve product quality, as well as other aspects in all lines of the company. Constraints that occur at PT. XYZ is a low boiler efficiency level, which is in the range of 65%-75%. This value is 10% lower than the standard efficiency of boilers that use coal as fuel. The purpose of this study is to increase the optimization of the use of boiler fuel at the company PT. XYZ. By using the FMEA method and the New Seven Tools, the problems causing wasteful use of fuel can be mapped thoroughly, making it easier to understand the root of the problem, as well as looking for targeted improvement suggestions. The result is that it is known that there are 7 problems related to optimizing the use of coal fuel at PT. XYZ. Among them are the problem of 'High coal humidity' with a waste of Rp 7,036,281,797 per year, the problem of 'Steam pipe leaking' with a waste of Rp 1,323,800,301 per year, and the problem of 'Sootblow Superheater and Economizer not optimal' with a wasted cost of Rp 349,490. 375 per year